2019
DOI: 10.3390/rel10090532
|View full text |Cite
|
Sign up to set email alerts
|

One Religion, Two Tales: Religion and Happiness in Urban and Rural Areas of China

Abstract: Most previous studies performed in Western social contexts have revealed that religion can influence an individual’s sense of happiness. Few studies have sought to clarify the influence of religion in a Chinese social context, however, and there has been no study specifically about the potential differences in the dichotomous social environments of urban and rural areas in China. Via the nationwide survey data of the 2007 Spiritual Life Study of Chinese Residents (SLSC), this study examines the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In a previous study conducted in Iran [ 34 ], levels of religiosity of urban and rural residents differed significantly and the level of religiosity in rural residents tended to be higher relative to that in urban residents. A study conducted in China indicated that urban and rural residents could have different levels of individual or social motivation to practice religion and despite the hostile rural social environment, the religious residents tend to be more likely to report higher level relative to their peers in urban areas [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study conducted in Iran [ 34 ], levels of religiosity of urban and rural residents differed significantly and the level of religiosity in rural residents tended to be higher relative to that in urban residents. A study conducted in China indicated that urban and rural residents could have different levels of individual or social motivation to practice religion and despite the hostile rural social environment, the religious residents tend to be more likely to report higher level relative to their peers in urban areas [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies using nationally representative population samples found a positive relationship between religion and SWB in China (Chen and Williams 2016;He et al 2016;Lu and Zhang 2016). Zhang et al (2019) found that, regardless of affiliation with Buddhism or Protestantism, there is a significant positive association between religion and SWB among rural residents, whereas this association is insignificant among urban respondents.…”
Section: Religion Background In Chinamentioning
confidence: 89%
“…A high-quality team of international scholars designed the questionnaire and managed to collect the data through face-to-face interview surveys (ARDA (Association of Religion Data Archives)). The SLSC dataset provides a set of high quality about the spiritual and religious life of Chinese residents and until now is still the only national representative survey with such rich information for understanding the practice of religion in China (Lu and Gao 2017;Zhang et al 2019).…”
Section: Data Source and Samplementioning
confidence: 99%
“…They demonstrate that happiness is measured by the individual's valuing of his/her emotive, mental and intellectual life which is driven by two factors: subjective ones, including religion, and objective ones, involving physical matters: "Thus, religion influences religious peoples' subjective responses to objective factors" (Zhang et al, 2019, p. 3). Zhang et al (2019) maintain that "religious belief" increases individuals' happiness due to the meaningful interpretations it provides religious people with, which enable them to understand life events and the purposefulness of life (p. 3). Sami, at this stage of his life, lacks religiosity; yet, Muntaha's adequate understanding of Islam and her connection to God lead Sami to better understand life.…”
Section: The Spiritual Samimentioning
confidence: 99%